Telling Identities : The Californio testimonios - Sánchez, Rosaura (Book collections on Project MUSE., 1995)
Sánchez offers the first historical and literary analysis of thirty 1870s testimonios from the original Spanish-speaking settlers of Alta California. Telling Identities scrutinizes the role of gender, class, race, language, and ethnicity in group identity formation as it looks into history to help articulate the cultural politics of contemporary Chicano and Latino culture in the United States.